THE EFFECT OF COORDINATION, COMPETENCE, AND LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE IN REGIONAL GOVERNMENT ORGANIZATIONS IN BINTAN REGENCY THROUGH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE - Eka Maria Susanti; Ngaliman; Mohamad Gita Indrawan (CV. Radja Publika, 2025)
This study analyzes the influence of coordination, competence and leadership style on employee performance of Regional Government Organizations in Bintan Regency and examines the role of organizational commitment as an intervening variable. Based on SAKIP evaluation data issued by the Ministry of State Apparatus Empowerment and Bureaucratic Reform, the performance of Bintan Regency Government is still considered suboptimal, thus requiring improvement and commitment in performance management. This study uses a qualitative approach with data collection techniques through questionnaires distributed to 180 employees of Bintan Regency. The research findings reveal that improvement in competence and leadership style has a significant direct influence on employee performance and organizational commitment. Conversely, coordination is proven to have an insignificant influence on performance and organizational commitment, furthermore the indirect influence of coordination on performance mediated by organizational commitment is also insignificant. The proposed recommendations are to improve employee coordination by optimizing socialization activities, coordination and synergy, one data application and studies to support the work completion process in each field within the Regional Government Organizations of Bintan Regency.